Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Can someone help me with the first one pls

Can Someone Help Me With The First One Pls class=

Sagot :

Answer:

The answer of the first one is b

Step-by-step explanation:

going left is negative and going up is positive

Answer:

12. a

13a. (-3, 2)

13b.[tex]12\sqrt{2}[/tex]

13c. [tex]( x +3 )^2 + ( y - 2 )^2 = 288[/tex]

Step-by-step explanation:

13a. Graph endpoints and find the center, and to find the center we can use the midpoint formula.

[tex]midpoint = (\frac{x_1+x_2}{2},\frac{y_1+y_2}{2})\\ = (\frac{-9+3}{2},\frac{-4+8}{2})\\= (\frac{-6}{2},\frac{4}{2})\\ = (-3,2)[/tex]

13b. Use given points and use distance formula to find radius.

[tex]distance = \sqrt{({x_2-x_1})^2+({y_2-y_1})^2}\\= \sqrt{({3-(-9)})^2+({8-(-4)})^2}\\= \sqrt{({3+9})^2+({8+4})^2}\\=\sqrt{({12})^2+({12})^2}\\ =\sqrt{({12})^2+({12})^2}\\= \sqrt{144+144} = \sqrt{288} = 12\sqrt{2}[/tex]

13c. Refer back to 13a and 13b to setup the equation of the circle.

[tex]( x - h )^2 + ( y - k )^2 = r^2\\( x - (-3) )^2 + ( y - 2 )^2 = (12\sqrt{2})^2\\( x +3 )^2 + ( y - 2 )^2 = 288[/tex]

Sorry if it looks long but I hope that helps!